Polish parents’ views on mathematics activities at home and in Swedish preschools - Lembrér, Dorota (NOMAD Nordic Studies in Mathematics Education, 2018)
This article describes the results of a digital survey of 41 Polish immigrant parents’ views on mathematics activities at home and at preschool as parents’ views potentially provide a range of perspectives on mathematics activities for young children. Parents were asked to describe and justify their views about how children engage with mathematical ideas and nominate activities that children engage in at home and at preschool. When parents justified their views about young children and mathematics, they tended to align themselves with the norms and values of the Swedish preschool curriculum. The findings suggest that parents, like children, are socialised into Swedish preschools. However, this alignment could limit possibilities for broadening perspectives about mathematics education in preschool, which could be available by incorporating input from immigrant parents’ different cultural and linguistic backgrounds.